Sosialisasi Pencegahan Pernikahan Usia Anak di Desa Kembang Kerang Daya - Sunardi, Sunardi; Setiani, Eli; Wati, Seni; Utama, Wawan Kurnia (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
This activity aims to provide understanding and awareness to the community about efforts to prevent people from getting trapped in underage marriages. This service was carried out in the form of socialization on the prevention of child marriage which took place in Kembang Kerang Daya Village. This activity will take place on October 23 2024. The targets of this activity are representatives from regional heads throughout Kembang Kerang Daya Village, representatives of health cadres, representatives of village institutions, and representatives of women's communities. The service approach used is Participatory Action Research (PAR) with three stages. 1) The preparation stage includes data collection and interviews with the families and children involved, as well as analysis of factors causing child marriage, such as promiscuity and limited education. 2) In the implementation stage, the service and partners deliver material regarding marriage regulations, the negative impacts of early marriage, and preventive measures, including changes to laws and regulations regarding the minimum age for marriage. 3) The evaluation stage is carried out to assess community understanding of the socialization material and to plan follow-up actions such as forming a prevention team, providing a budget, revising village regulations, and drafting child protection regulations.